Pemanfaatan Hidrotherapy Jahe Merah untuk Menurunkan Tekanan Darah pada Keluarga di Kelurahan Legok - Miko Eka Putri; Mila Triana Sari (Jurnal Abdimas Kesehatan (JAK), 2023)
Based on profile data from Jambi Province, it shows that the incidence of hypertension ranks first from 2018 to 2020. The increasing incidence of hypertension requires community nurses to teach the public how to treat it with red ginger hydrotherapy. Research Before results show that red ginger hydrotherapy has an effect on blood pressure. For this reason, it is necessary to carry out community service regarding the use of red ginger hydrotherapy to treat hypertension problems. This service aims to provide education to the public on how to treat hypertension with red jehe hydrotherapy. This service will be carried out on 22-25 May 2022 to 15 people in Legok Village, Jambi City. The method for implementing this activity is 1). Pretest 2). Providing education about how to treat hypertension with red ginger hydrotherapy, 3). Post test. Education is carried out for 60 minutes. Based on the results of checking the highest systolic blood pressure before treatment was 180 mmHg and the lowest 140 mmHg, while the results of measuring diastolic blood pressure it can be concluded that the highest blood pressure before treatment was 100 and after giving hydrotherapy there was the highest change, namely 80 mmHg. These results indicate that there was a change in blood pressure after administering red ginger hydrotherapy. So red ginger hydrotherapy can be recommended as a therapy for hypertensive patients. For further service, research on red ginger and salt hydrotherapy to treat hypertension is recommended